Developing Body Awareness, Social Interaction, and Creativity through Mind Muscle Exercises in Dance Learning: A Case Study at SDN Pulorejo 1 Jombang - Ratih Asmarani; Agus Cahyono; Djuli Djatiprambudi; Eko Sugiarto (Universitas Nahdatul Ulama Surabaya, 2026)
Elementary dance education is commonly delivered through imitation and rote memorization, thereby constraining opportunities for children to develop body awareness, social interaction, and creative movement exploration. Although creative dance has been extensively theorized, the integration of mind–muscle exercises as an embodied pedagogical approach in elementary dance learning remains insufficiently examined. This study investigates how mind–muscle exercises facilitate the development of body awareness, social interaction, and creativity among primary school students in dance education. A qualitative case study was conducted at SDN Pulorejo 1 Jombang, involving 26 first-grade students. Data were collected through classroom observations, semi-structured interviews, documentation, and field notes and subsequently analyzed using thematic analysis. The findings indicate that mind–muscle exercises significantly enhanced students’ awareness of body parts, movement quality, spatial orientation, and energy regulation, enabling more intentional and confident movement execution. Moreover, the activities fostered meaningful social interaction through processes of imitation, collaboration, negotiation, and collective movement composition. Creativity emerged dynamically throughout the learning process, as students actively explored, modified, recombined, and expressed original movement ideas rather than merely replicating teacher demonstrations. These findings suggest that mind–muscle exercises operate as an effective embodied pedagogical strategy, repositioning the child’s body from a passive object of imitation to an active subject of exploration, interaction, and creative expression. This study contributes to the field of elementary dance pedagogy by offering an exploratory, participatory, and body-awareness-oriented instructional model that supports embodied learning and the development of creativity in primary education contexts.